1994
DOI: 10.1021/bi00252a026
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization of the c-myb DNA-binding domain

Abstract: We have examined proteins containing the DNA-binding domain of c-Myb with biophysical methods. This DNA-binding domain consists of three imperfect repeats (R1, R2, and R3) conserved among many species. Our results indicate that the DNA-binding domain forms unspecific and specific complexes with oligodeoxynucleotides. In the presence of R1, DNA sequences related to a canonical c-Myb-binding site are better discriminated. Furthermore, although R2 and R3 are sufficient for sequence-specific DNA binding, a structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
6
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
5
6
1
Order By: Relevance
“…EMSA experiments confirmed that at high concentrations bMYB305 indeed bound to mutated MRE cHs probes (data not shown). Similar observations have been made with cMYB (Ebneth et al, 1994).…”
Section: Pcmybi Interacts In Vivo With Mre Chssupporting
confidence: 88%
“…EMSA experiments confirmed that at high concentrations bMYB305 indeed bound to mutated MRE cHs probes (data not shown). Similar observations have been made with cMYB (Ebneth et al, 1994).…”
Section: Pcmybi Interacts In Vivo With Mre Chssupporting
confidence: 88%
“…The minimal region of c‐Myb that is both necessary and sufficient for sequence‐specific DNA‐binding has been narrowed down to repeats R2 and R3 [7,10–12] and unlike many other sequence‐specific DNA‐binding proteins, the Myb proteins appear to bind to DNA as monomers [10,11]. Though repeat R1 was not shown to be involved in sequence‐specific recognition, it has been suggested to increase the affinity of the protein for DNA and the stability of the Myb‐DNA complex [13–17].…”
Section: Introductionmentioning
confidence: 99%
“…The Myb DNA-binding domain comprises three imperfect tandem repeats (R1, R2, and R3), each forming a tri-helical protein fold in which an HTH motif is formed by helix 2 and 3 (32,33). Together, R2 and R3 are sufficient for recognition of specific DNA sequences, whereas R1 enhances the stability of the Myb-DNA complex (34,35). The three helices in each repeat are maintained by a hydrophobic core that includes three strictly conserved tryptophan residues ( Fig.…”
mentioning
confidence: 99%